Ballistic missile defense - Carter, Ashton B.; Schwartz, David N., 1956- (Brookings Institution, 1984)
Defense against nuclear attack--so natural and seemingly so compelling a goal--has provoked debate for at least twenty years. Ballistic missle defense systems, formerly called antiballistic missile systems, offer the prospect of remedying both superpowers' alarming vulnerability to nuclear weapons by technological rather than political means. But whether ballistic missile defenses can be made to work and whether it is wise to build them remain controversial. The U.S.-Soviet Anti-Ballistic Missile Treaty of 1972 restricts testing and deployment of ballistic missile defenses but has not prohibit.